Clinical effectiveness of liraglutide on weight loss in South Koreans: First real-world retrospective data on Saxenda in Asia - Park, Joon Seok; Kwon, Jieun; Choi, Hyung Jin; Lee, Changhyun (Medicine (Baltimore), 2021)
Among Asian countries, South Korea was the first to approve liraglutide as a treatment for obesity. Thus, the clinical effectiveness of liraglutide has not been studied in Asian populations.In this study, we retrospectively analyzed obese patients [body mass index (BMI) >27 kg/m2] who were treated with liraglutide between March 2018 and March 2019 in a single clinic. Weight, BMI, HbA1c, and clinical data were collected before liraglutide treatment. Changes in body weight and composition and their relationships with clinical variables were examined at re-prescription dates within 30, 60, 90, and 180 days.A total of 169 subjects were studied. The average age was 41.5 years, and 42% of the subjects were male. The average weight was 85.2 kg, and the average BMI was 30.8 kg/m2. Weight reduction was significant (-5.5 ± 3.4 kg, 30 days: -3.2 ± 1.8 kg, 60 days: -4.5 ± 2.3 kg, 90 days: -6.3 ± 2.6 kg, 180 days: -7.8 ± 3.5 kg) during the follow-up period and increased with longer treatment time (P < .001). The percentages of subjects that showed ≥ 5% and ≥ 10% body weight reduction were 62.1% and 17.2%, respectively. In the body composition analysis, skeletal muscle weight loss was -3.56 ± 29.7%, which was significantly smaller than fat weight loss of -11.06 ± 10.4% (P = .03). Weight loss was not significantly related to age, sex, baseline BMI, baseline HbA1c, smoking status, alcohol consumption, coffee intake.In conclusion, Liraglutide treatment led to meaningful weight loss in South Korean patients, and fat mass reduction was prominent during treatment. Furthermore, liraglutide showed greater clinical effectiveness with longer treatment time.